Measuring the performance of assets: a review of the Facility Condition Index - Re Cecconi, Fulvio; Moretti, Nicola; Dejaco, Mario Claudio (International Journal of Strategic Property Management, 2019)
Measurement of performances in asset management is an enabling factor to define an effective strategy. The scope of this research concerns the investigation on the Facility Condition Index (FCI): one of the most common metrics related to the built environment. The research aims at providing a critical review concerning the FCI and its use. The research methodology has been developed according to three steps: bibliographic research, bibliometric analysis and critical review. Most of the sources agree that FCI provides a reliable economic measurement of maintenance needs, though it must be tied to a strong condition assessment methodology. Moreover, different methodologies for computation of the deferred maintenance and the current replacement value can be found in literature and many researchers emphasised the limits of FCI when dealing with components characterised by a considerable difference in replacement costs. In conclusion, FCI is included in the wider framework of asset management business process.